Acute Respiratory Distress Syndrome in a Patient with Myasthenia Gravis and Septic Shock: A Case Report - Nur Amin, Taufiqurrochman; Septian Adi Permana (HM Publisher, 2024)
Introduction: Myasthenia gravis (MG) is an autoimmune disorder characterized by muscle weakness, often affecting respiratory and oropharyngeal muscles. This predisposition to respiratory compromise, coupled with impaired swallowing and the potential need for immunosuppressive therapies, increases the risk of pneumonia and subsequent sepsis in MG patients. Sepsis, in turn, is a significant risk factor for acute respiratory distress syndrome (ARDS), a severe lung condition with high mortality. Case presentation: We present the case of a 47-year-old male with a 4-year history of MG who was admitted to our hospital with progressive dyspnea and dysphagia. His condition deteriorated rapidly, leading to septic shock and respiratory failure necessitating invasive mechanical ventilation. Blood cultures identified Klebsiella pneumoniae with extended-spectrum beta-lactamase (ESBL) production. Despite aggressive treatment, including therapeutic plasma exchange (TPE), the patient's hospital course was complicated. Conclusion: This case underscores the critical importance of vigilant monitoring and early intervention in MG patients presenting with respiratory symptoms or signs of infection. Prompt recognition and aggressive management of sepsis are crucial to mitigate the risk of ARDS and improve outcomes in this vulnerable patient population.